Varieties of Unbelief: A Taxonomy of Atheistic Positions - Vainio, Olli-Pekka (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2015)
In this article, we provide a classification of contemporary atheism based on the kinds of worldviews and beliefs atheists hold. We suggest that at least four general types of atheism can be distinguished: scientistic atheism, philosophical atheism, tragic atheism and humanistic atheism, which can then be divided to various subclasses. With this classification, we aim to challenge the view that atheism is not a belief system but merely the lack of belief in some transcendent being. Moreover, there seems to be no single atheism per se, instead there are many atheistic worldviews that include a number of positive beliefs and motivate their atheism in different ways.